Exploring German Secondary School Students’ Conceptual Knowledge of Density - Zenger, Tim; Bitzenbauer, Philipp (Science Education International, 2022)
This article reports on the development and piloting of a German version of a concept test to assess students’ conceptual knowledge of density. The concept test was administered in paper-pencil format to 222 German secondary school students as a post-test after instruction in all relevant concepts of density. We provide a psychometric characterization of the instrument based on the student responses. Therefore, we use methods from classical test theory and item response theory. Our analysis shows that our concept test has good psychometric properties. Furthermore, it is shown to enable a reliable (α= 0.77) survey of students’ conceptual knowledge of density. Finally, we use the student responses to identify secondary school students’ difficulties with the density concept. We replicate student difficulties on density from the literature, but our study also reveals some new difficulties.<br
Keywords: concept inventory; student difficulties; density